Analisis Modernisasi Sistem Administrasi Perpajakan Dalam Kepatuhan Wajib Pajak Badan Pada Kantor Pelayanan Pajak Madya Makassar - Syam, Hasnidar; Wahyuni, Nur (Jurnal Online Manajemen ELPEI, 2024)
The method used in this research is descriptive quantitative. Data collection was carried out using a questionnaire. The total population in this study were 2,046 thousand corporate taxpayers registered at the Makassar Madya KPP. The population is relatively large (2,046 people), so sampling using the Slovin formula in order to obtain 100 respondents. The data analysis techniques used are data quality test, classical assumption test, and hypothesis testing using the SPSS program. The results of this study found that account representative performance has a positive and significant effect on taxpayer compliance. The better the account representative's performance, the more taxpayer compliance will be. The application of e-system has a positive and significant impact on taxpayer compliance. The better the application of the e-system, the taxpayer compliance will increase. The most dominant variable affecting corporate taxpayer compliance is account representative performance which has a standard coefficient beta value of 0.759.